Accessory renal arteries: a case report - Babu, Billakanti Prakash; Roy, Anjali; Bangera, Hemalatha (International Journal of Research in Medical Sciences, 2017)
During dissection of abdomen by the undergraduate medical students three accessory renal arteries were observed on the right side. The superior accessory artery was a small vessel arising from aorta just above the normal renal artery. It entered the anterior surface of kidney just below the upper pole. The middle and inferior arteries were caudal to the normal renal artery. The middle artery was arising from testicular artery and entered the anterior surface of kidney below the hilum. The inferior artery was arising from aorta just above its bifurcations and entered the lower pole of kidney. The importance of accessory renal arteries in surgical procedures of the posterior abdominal wall and renal transplantation are discussed.